Development of Interactive Learning Media Using Adobe Flash on the Subject of Electronic Control Systems - Hariyanto, Agus; Fatirul, Ach. Noor; Harwanto, Harwanto (Lembaran Ilmu Kependidikan, 2024)
At the vocational school level, pneumatic basic competency is one of the basic competencies in the Electronic Control Systems subject. This basic competency is fundamental and must be mastered by class XI SMK students in the Industrial Electronics Engineering Skills Competency. This research aims to produce basic pneumatic interactive learning media in the form of an interactive CD that is suitable for the Electronic Control Systems subject for class XI students at SMKN 1 Jetis Mojokerto. This research is a type of Research and Development (R&D) research to produce a learning product that suits your needs. The research steps refer to the Borg and Gall  model to produce systematic and structured research. Meanwhile, the steps for developing interactive learning media using Adobe Flash in electronic control system subjects, pneumatic basics material refers to the ADDIE model to produce quality learning media that suits learning needs. Interactive Learning Media Using Adobe Flash in the Subject of Electronic Control Systems, this pneumatic material was validated by design experts, media experts, material experts, colleagues and students. The design expert validation results obtained a percentage of 88.18% in the very valid category, media expert validation obtained a percentage of 85.71% in the very valid category, material expert validation obtained a percentage of 89.23% in the very valid category, peer assessment obtained the percentage was 92.5% with a very valid category, small group product trials involving 5 students were 90%, medium group trials of 9 students were 90.22%, large group trials by 36 students got a percentage of 91.00 %, while for field trials involving 70 students with a percentage of 91.04%. So this media is said to be very valid and feasible and can be used as an alternative media in learning. This study contributes to improving vocational education by developing interactive learning media for pneumatic basics, which enhances student engagement and competency in electronic control systems.